Pengembangan Metode Pembelajaran Problematics And Work Projects Dalam Pembelajaran Jarak Jauh (Distance Learning) Untuk Meningkatkan Pemahaman Peserta Didik Terhadap Materi Pelajaran Ekonomi Peminatan - Naila Riza Umami; Maria Aghata Sri Widyanti Hastuti; Diana Nur Santi (Universitas Hamzanwadi, 2021)
This research is motivated to solve problems that occur in online learning and learning activities (Distance Learning) caused by the spread of the covid-19 virus throughout the world. This research is to develop an appropriate learning model and can be used in online learning activities (Distance Learning) with specialization economics material with Basic Problematics And Work Projects with research methods in the form of Research And Development or as the RnD method. This study aims to solve problems that have occurred in the school environment where educators, namely teachers, experience several problems in these activities which result in stagnation in learning activities and have a direct impact on students who are taught learning materials both theoretically, psychologically and sociologically. . Problems experienced by educators, namely teachers, such as being less precise in the selection and use of learning methods used in teaching and learning activities as well as educators, namely teachers experiencing difficulties in using online and online-based learning media (Distance Learning) which resulted in problems among participants. students in the form of, lack of absorption of students to the material being taught, lagging material, completion of structured tasks that are past the collection deadline and students feel the lack of material being taught. Therefore, this research was held to solve the problem with a final result of 79.65% with a suitable category for use with minor revisions.